Analisis Tingkat Kesehatan Bank Dengan Menggunakan Metode Risk Profile, Good Corporate Governance, Earnings, Capital (RGEC) Pada Bank Muamalat Periode 2013-2017 - Ade Yunita (Science of Management and Students Research Journal (SMS), 2020)
The purpose of this research is to determine the health rating of Bank Muamalat seen from Risk Peofile, Good Corporate Governance, Earnings, Capital (RGEC) aspects during 2013-2017. The data that used in this research  is secondary data, and the researcher take the  financial statements of Bank Muamalat in 2013-2017 as research source. The technique of data analysis that used is the analysis technique of bank health using the Risk approach (Risk Based Bank Rating/RBBR) with the scope of the assessment. There are 4 factors that must be analyzed and it is: Risk Profile, Good Corporate Governance (GCG), Profitability (Earnings), Capital (Capital) or usually called RGEC method. The research took the object of research of Bank Muamalat on the grounds that he was interested in seeing Bank Muamalat company becoming opioneer of Islamic banking in Indonesia, this is because Islamic bank were able to obtain and target large markets with the application of its syari’ah system, namely by ensuringthat bank interest is haram. The research took the object of research of Bank Muamalat on the grounds that he was interested in seeing Bank Muamalat company becoming o pioneer of Islamic banking in Indonesia, this is because Islamic bank were able to obtain and target large markets with the application of its syari’ah system, namely by ensuringthat bank interest is haram. The results of the assessment of the health rating of Bank Muamalat as a whole seen from the aspect of Risk Profile, Good Corporate Governance, Earnings, Capital (RGEC) during 2013-2017 was in a “healthy enough’’ condition. So that the bank during the period, Bank Muamalat was considered able to deal with significant negative effects of changes in business conditions and other external factors, but when viewed more in each ratio of the assessment indicators, there were several assessment which show criteria that Bank Muamalat were quite healty and even unhealthy. The after conducting on the analysis of health level assessment of  Bank Muamalat using the RGEC method of  Bank Muamalat period with standards set by the financial services authority (OJK) for the period 2013-2017 it can be concluade that Bank Muamalat  composite rating is “Healty Enough”.